TiO(2)@Cu(2)O n-n Type Heterostructures for Photochemistry - Trenczek-Zajac, Anita (Materials (Basel), 2021)
A TiO(2)@Cu(2)O semiconductor heterostructure with better photochemical response compared to TiO(2) was obtained using an electrochemical deposition method of Cu(2)O on the surface of TiO(2) nanotubes. The choice of 1D nanotubes was motivated by the possibility of achieving fast charge transfer, which is considered best suited for photochemical applications. The morphology and structural properties of the obtained heterojunction were determined using standard methods —SEM and Raman spectroscopy. Analysis of photoelectrochemical properties showed that TiO(2)@Cu(2)O heterostructures exhibit better properties resulting from an interaction with sunlight than TiO(2). A close relationship between the morphology of the heterostructures and their photoproperties was also demonstrated. Investigations representing a combination of photoelectrochemical cells for hydrogen production and photocatalysis—photoelectrocatalysis—were also carried out and confirmed the observations on the photoproperties of heterostructures. Analysis of the Mott–Schottky plots as well as photoelectrochemical measurements (I(ph)-V, I(ph)-t) showed that TiO(2) as well as, unusually, Cu(2)O exhibit n-type conductivity. On this basis, a new energy diagram of the TiO(2)@Cu(2)O system was proposed. It was found that TiO(2)@Cu(2)O n-n type heterostructure prevents the processes of photocorrosion of copper(I) oxide contained in a TiO(2)-based heterostructure.